2020
DOI: 10.1152/japplphysiol.00081.2020
|View full text |Cite
|
Sign up to set email alerts
|

Greater lactate accumulation following an acute bout of high-intensity exercise in males suppresses acylated ghrelin and appetite postexercise

Abstract: We used sodium bicarbonate to increase lactate accumulation or sodium chloride as a placebo. Our findings further implicate lactate as a mediator of exercise-induced appetite suppression given exercise-induced increases in lactate during the sodium bicarbonate session altered peripheral concentrations of appetite-regulating hormones, culminating in a reduction of appetite. This supports a lactate-dependent mechanism of appetite suppression following high-intensity exercise and highlights the potential of using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 55 publications
4
24
1
Order By: Relevance
“…For instance, few are hungry immediately after maximal exercise to exhaustion. The suppressive effect of lactate on appetite suppression (Schmid et al, 2008;Schultes et al, 2012;McCarthy et al, 2020) is consistent with results that lactatemia results in appetite suppression via ghrelin secretion (Islam et al, 2017;Vanderheyden et al, 2020). The ghrelin receptor [growth hormone secretagogue receptor (GHSR-1) is a G-protein coupled receptor expressed throughout both the stomach and GI tract.…”
Section: Lactate Shuttling Into the Future: Unresolved Issues And Futsupporting
confidence: 81%
“…For instance, few are hungry immediately after maximal exercise to exhaustion. The suppressive effect of lactate on appetite suppression (Schmid et al, 2008;Schultes et al, 2012;McCarthy et al, 2020) is consistent with results that lactatemia results in appetite suppression via ghrelin secretion (Islam et al, 2017;Vanderheyden et al, 2020). The ghrelin receptor [growth hormone secretagogue receptor (GHSR-1) is a G-protein coupled receptor expressed throughout both the stomach and GI tract.…”
Section: Lactate Shuttling Into the Future: Unresolved Issues And Futsupporting
confidence: 81%
“…Moreover, it has been reported that exercise intensity may differentially affect physiological mechanisms involved in appetite regulation. While low-and moderate-intensity exercise appear to have little impact on appetite perception 73 , it has been demonstrated that high-intensity exercise may have appetite-suppressing effects, which were associated with exercise-induced changes in peripheral gut hormones like ghrelin 74 and modifications in brain receptors controlling central appetite regulation 75 . The observed greater (although not statistically significant) reduction of energy intake in the HIIT group compared www.nature.com/scientificreports/ to the MIIT group supports these previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have compellingly demonstrated that higher intensity (>75% V _ O 2max ) exercise elicits larger reductions in ghrelin and appetite, which favor reduced EI in the hours after exercise (22,25,46). Although the mechanisms explaining the greater appetite suppressive effects of high-intensity exercise remain largely uninvestigated (22), recent work from our laboratory (25,49) and others (19,20,46) supports lactate as a key mediator of exercise-induced appetite suppression. For instance, acute supramaximal ($170% V _ O 2max ) interval cycling elicits greater reductions in ad libitum (70 min postexercise) and free living (38 h postexercise) EI in overweight males, subsequent to lower ghrelin (À30%) and higher blood lactate levels (+6 mmol/ L) compared with lower intensity (60% V _ O 2peak ) exercise (46).…”
Section: Evidence Supporting a Role For Lactate In Exercise-mediated Appetite Suppressionmentioning
confidence: 96%
“…Although the role of lactate in these various processes has garnered significant attention (5), another relatively underexplored role of lactate is its apparent influence on appetite and subsequent energy intake (EI). In this regard, a number of recent human studies from our laboratory (25,49) and others (19,20,46) implicate lactate as an important mediator of exercise-induced appetite suppression. Intuitively, since the intensity-dependent production of lactate from exercising muscle reflects metabolic demand (5), the concept of lactate as a musclederived signal mediating appetite suppression is logical.…”
Section: Introductionmentioning
confidence: 98%